Effect of Multi-Walled Carbon Nanotubes on Physiological Traits, Phenolic Contents and Antioxidant Capacity of Salvia mirzayanii Rech. f. & Esfand. under Drought Stress (Institue of Medicinal Plants, ACECR, 2017)
Background: Environmental stresses and biotic and abiotic elicitors induce secondary metabolites biosynthesis and hypersensitive response in plants through activation of defense mechanisms.   Aim: This study was carried out with the aim of assessing the effects of different drought stress and multi-walled carbon nanotubes (MWCNTs) levels on physiological variations, flavonoid and phenolic contents, and antioxidant capacity of Salvia mirzayanii. Methods: This study was arranged in a factorial experiment based on randomized complete block design under research greenhouse of medicinal plants department at Arak University. The first factor was considered as drought stress in 4 levels including 100, 75, 50 and 25% of field capacity (FC), and the second factor was designated as foliar spray of MWCNTs (functionalized and non- functionalized) at 4 different concentrations (0, 50 and 200 mg/L for functionalized MWCNTs, and 50 mg/L for non- functionalized MWCNTs). Results: Results showed that drought stress and MWCNTs and their interactions significantly affected some studied traits. Leaf relative water content (p < 0.01) and chlorophyll index (p < 0.05) was significant under drought stress treatment, however, electrolyte leakage index significantly (p < 0.01) changed under different levels of MWCNTs. Furthermore, total phenolics was significantly (p < 0.01) changed under interaction of experimental treatments. The highest and the lowest phenolics content were achieved in functionalized MWCNTs exposed plants at 50 and 200 mg/L under 25% of FC, respectively. Maximum antioxidant activity was observed in extract originated from plants simultaneously treated with functionalized MWCNTs at 50 mg/L and drought stress at level of 25% FC.  Conclusion: Application of functionalized MWCNTs at concentration of 50 mg/L along with moderate drought stress improved physiological traits and antioxidant activity of extract in S. mirzayanii plants.